Les ailes de l’abeille - Adrienne Dupont-Hamy (Mélanges de la Casa de Velázquez)
Juan Gil is a Franciscan encyclopaedist from Zamora. His floruit dates to the end of the 13th century. Amongst the hid numerous works, we will focus on his Historia naturalis. The analysis of its rubrics shows its entanglement with homiletics (the homiletic touch is also at work, surprisingly sometimes, in other egidian compilations). Holy Scripture plays a key role in the egidian quaestiones naturales, namely through a moralization process that uses various exegetic tools: subdivisions and distinctions, concordances, interpretations, similitudines and sermons. How can they be defined? What hermeneutics are they serving? What place and role does exegesis occupy in Juan Gil’s encyclopaedic and homiletic activities? This contribution aims to shed light on the matter.